(untitled) - Osborn, Annaa (Thành phố Hồ Chí Minh, 2014)
The book has 20 units devided into four sections : Emails; Doing business; Marketing and advertising; Business media and book
Keywords: English language,Tiếng Anh; Study and teaching,Dạy và học